Analisis Manajemen Laba yang Dipengaruhi oleh Komite Audit dan Firm Size Perusahaan LQ 45 Tahun 2015 - 2019 - Rakhmawati Oktavianna; Eka Rima Prasetya (Jurnal Ilmiah Akuntansi Universitas Pamulang, 2021)
ABSTRACTManagers manipulate earnings by increasing the number of reported earnings so that earnings information about the company becomes a good signal for investors to invest their shares and increase trust in creditors. The purpose of this study is to examine the effect of the audit committee and firm size on earnings management at LQ45 companies listed on the Indonesia Stock Exchange (BEI) in 2015 - 2019. The type of research in this study uses a quantitative approach. Data collection using the document method with secondary data sources. Determination of the sample using purposive sampling method, with a total sample of 130 samples. The data analysis technique used is the multiple linear regression test using the program Eviews 10. The results of this study are that the audit committee and firm size together have an effect on earnings management, the audit committee has no effect on earnings management and firm size has an effect on earnings management in the company. LQ45 which is listed on the Indonesia Stock Exchange (IDX) in 2015 - 2019.